KAJIAN HUKUM TERHADAP SUBSIDI UPAH BAGI PEMEGANG BPJS KETENAGAKERJAAN PADA MASA PANDEMIC COVID-19 MENURUT KONSTITUSI DI INDONESIA - Permai Yudi, S.H.,M.H (Universitas Quality, 2021)
Research on Legal Studies on Wage Subsidies for BPJS Ketenagakerjaan holders according to the Constitution in Indonesia (Salary/Wage Subsidies for Workers/Workers in Handling the Impact of Covid-19), this study aims to describe the legal basis for the policy of the Wage Subsidy program in the implementation of the Cash Direct Assistance (BLT) program in Indonesia during the Handling of the Impact of Corona Virus Disease 2019 (Covid-19). Research uses normative research methods. The implementation of BLT program is running well, orderly, smoothly, and safely. In the implementation of the program, data verification, disbursement of funds. Factors that support and hinder the successful implementation of the program are companies or employers who do not report workers / employees who are paid under 5 (five) million, become obstacles in the distribution of blt funds what else those who work do not have BPJS Employment, which becomes a barrier when it is, the political situation that supports and rejects the program, and the need for proper and accurate coordination between the implementers of the program and who still need to be legalized or involve institutions outside the government.